Microsporidian genome analysis reveals evolutionary strategies for obligate intracellular growth - Cuomo, Christina A.; Desjardins, Christopher A.; Bakowski, Malina A.; Goldberg, Jonathan; Ma, Amy T.; Becnel, James J.; Didier, Elizabeth S.; Fan, Lin; Heiman, David I.; Levin, Joshua Z.; Young, Sarah; Zeng, Qiandong; et al. (Genome Research, 2012)
Microsporidia comprise a large phylum of obligate intracellular eukaryotes that are fungal-related parasites responsible for widespread disease, and here we address questions about microsporidia biology and evolution. We sequenced three microsporidian genomes from two species, Nematocida parisii and Nematocida sp1, which are natural pathogens of Caenorhabditis nematodes and provide model systems for studying microsporidian pathogenesis. We performed deep sequencing of transcripts from a time course of N. parisii infection. Examination of pathogen gene expression revealed compact transcripts and a dramatic takeover of host cells by Nematocida. We also performed phylogenomic analyses of Nematocida and other microsporidian genomes to refine microsporidian phylogeny and identify evolutionary events of gene loss, acquisition, and modification. In particular, we found that all microsporidia lost the tumor-suppressor gene retinoblastoma, which we speculate could accelerate the parasite cell cycle and increase the mutation rate. We also found that microsporidia acquired transporters that could import nucleosides to fuel rapid growth. In addition, microsporidian hexokinases gained secretion signal sequences, and in a functional assay these were sufficient to export proteins out of the cell; thus hexokinase may be targeted into the host cell to reprogram it toward biosynthesis. Similar molecular changes appear during formation of cancer cells and may be evolutionary strategies adopted independently by microsporidia to proliferate rapidly within host cells. Finally, analysis of genome polymorphisms revealed evidence for a sexual cycle that may provide genetic diversity to alleviate problems caused by clonal growth. Together these events may explain the emergence and success of these diverse intracellular parasites.
10.1101/gr.142802.112